2016
DOI: 10.1016/j.dnarep.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical actions of mismatch repair

Abstract: At the heart of the mismatch repair (MMR) system are proteins that recognize mismatches in DNA. Such mismatches can be mispairs involving normal or damaged bases or insertion/deletion loops due to strand misalignment. When such mispairs are generated during replication or recombination, MMR will direct removal of an incorrectly paired base or block recombination between nonidentical sequences. However, when mispairs are recognized outside the context of replication, proper strand discrimination between old and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 92 publications
(118 reference statements)
0
25
0
1
Order By: Relevance
“…MutS and MutL homologs are also involved in DNA metabolic processes other than canonical mismatch repair [91]. Some of these promote genome stability, such as suppression of homeologous recombination (by disrupting exchange between heteroduplex DNA substrates) [12,92], while others promote genome instability, such as expansion of triplet nucleotide repeat (TNR) sequences [93], processing of DNA oxidative damage lesions [94], and somatic hypermutation for antibody diversity [95].…”
Section: Ongoing Research On How Atpase-coupled Actions Of Muts Anmentioning
confidence: 99%
“…MutS and MutL homologs are also involved in DNA metabolic processes other than canonical mismatch repair [91]. Some of these promote genome stability, such as suppression of homeologous recombination (by disrupting exchange between heteroduplex DNA substrates) [12,92], while others promote genome instability, such as expansion of triplet nucleotide repeat (TNR) sequences [93], processing of DNA oxidative damage lesions [94], and somatic hypermutation for antibody diversity [95].…”
Section: Ongoing Research On How Atpase-coupled Actions Of Muts Anmentioning
confidence: 99%
“…As discussed in more detail elsewhere in this issue [20], DNA repair of base damages, including mismatched uracils, relies on the MMR and BER pathways [21, 22]. Canonical MMR uses a heterodimer complex formed by either MutSα, consisting of MSH2 and MSH6, or MutSβ, formed by MSH2 and MSH3, to recognize and bind to mismatches.…”
Section: Introduction To Aid and Canonical Dna Repairmentioning
confidence: 99%
“…Studies in model organisms and human cells have demonstrated that the MMR system has multiple functions in DNA metabolism ((116), and other reviews in this special issue). Most functions of the MMR system promote genome stability, but some of its functions contribute to the instability of certain genomic loci (7,17,18). Repair of DNA mismatches that are formed during replication and homologous recombination is the major genetic stabilization function of the MMR system (19–25).…”
Section: Introductionmentioning
confidence: 99%
“…The most common substrates for the MMR system are small DNA insertion/deletion loops and single DNA base-base mispairs (2729). The MMR system also corrects DNA mispairs containing 8-oxoguanine and other oxidatively damaged bases (17,3033). Furthermore, the MMR system removes 1-nucleotide Okazaki fragment flaps (34) and single ribonucleotides, which are incorporated into DNA opposite noncomplementary deoxyribonucleotides (35).…”
Section: Introductionmentioning
confidence: 99%